Dampak strategi membaca generatif cerita fiksi berbasis platform sastra digital noveltoon terhadap kreativitas mahasiswa - Pratomo, Nugroho Widhi; Yanti, Prima Gusti; Sukardi, Sukardi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study investigates the impact of a generative reading strategy for fictional stories, specifically utilizing the Noveltoon digital literature platform, on language knowledge and language creativity. A quasi-experimental method involving 220 university students was employed. Data analysis utilized a t-test and a one-way ANCOVA to examine the intervention's influence on students' language creativity when writing short stories and creating reading tabloids after engaging with fictional stories. The findings indicate that the generative reading strategy, integrated with the Noveltoon digital literature platform technology and online platforms, significantly enhances students' language knowledge and creativity compared to traditional reading methods. The enhancement in students' creativity is evident in their ability to produce original short stories and create engaging reading tabloids following the reading intervention. Specifically, the increase in language creativity was observed across the dimensions of fluency, flexibility, originality, and elaboration. This study suggests that integrating a generative reading strategy for fictional stories with technology use can substantially improve the quality of the learning process and the development of students' language creativity.